Evaluating a nutrition education programme for food service assistants in pre-schools in the Vaal Region - Spillman, Rene. (My University, 2010)
Malnutrition amongst pre-school children age two-to-five-years is a growing world-wide concern. This is mainly due to poverty, diseases and inadequate dietary intake. Malnourished children are also a problem in South Africa. Pre-schools play an important role in the prevention of malnutrition because most young children consume about two thirds of their food and therefore their daily nutritional intake at the pre-schools. There are various factors that affect a child's nutrition in pre-schools, such as food choices, meal plans, the environment and the nutritional knowledge of the caregivers. Pre-schools can only fulfill this responsibility through the proper nutritional knowledge and training. The nutritional education and knowledge of food service assistants/caregivers are very important, because they compile the meal plans and menus for pre-schools. The objectives of this study were to evaluate a Nutrition Education Programme (NEP) to address the lack of nutritional knowledge of service assistants/caregivers who plan the menus in pre-schools in terms of existing menu content and food choices required for children between two to five years of age and by using the existing menus and food choices applied to make recommendations for nutritional skills training. Also in terms of basic nutrition, health and safety, to recommend more appropriate alternatives acceptable to children between two to five years of age. Lastly to integrate recommendations for nutritional skill training with regard to the alternative meal plan, eating habits and food choices for the menu through a NEP that would be implemented and evaluated. The study design was a combination of an exploratory and quantitative-descriptive research design in the form of a survey. A pilot study was used mainly to test the nutrition knowledge questionnaires for content validity. The study population of this research project was randomly selected pre-schools chosen from the Eatonside informal settlement. Procedures for data gathering and the different methods used for data analysis were divided into four phases. Descriptive statistics were used to determine the percentage of pre-schools who answered the questions correctly for selected nutrition knowledge, portion sizes questions and menu planning, as well as food safety and health. Paired t-tests were carried out to measure the statistically significant difference (pS0.05) before and after the implementation of the NEP. The results of the t-test indicate that only nine of the questions in the post-test questionnaire showed a confidence interval of the difference. There is statistical significance in these questions through either increase or decrease. It can be concluded that the Nutrition Education Programme (NEP) was successful, but that more training is needed due to the limitations experienced. The menu analysis tested the respondent's menus in terms of the average daily nutrient intake level given to the pre-school children. The data of the pre- and post-test menus were then compared to EAR in order to determine any change in the menus nutritional values after the NEP was completed. The results showed that there were differences in the post-test results that both decreased and increased.
Thesis (M. Tech. - Food Service Management, Dept. of Hospitality, Tourism and PR management)--Vaal University of Technology
Keywords: Malnutrition; Pre-school children; Meal plans; Food choices; Nutrition Education Programme; Nutritional skills training; 614.59390968; Nutrition evaluation.; Nutrition education.